Wolność akademicka. Konteksty i rekonstrukcje = Academic freedom. Contexts and reconstructions - Melosik, Zbyszko (1956- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The understanding of academic freedom is the key to analyse both the essence as well as the functioning of the western university. Scientists and publicists, on one hand point out that the idea of academic freedom lies in the heart of political and academic struggle for the future of the university, on the other hand they agree that this freedom needs to be protected. In this article I attempt to answer numerous questions concerning the essence of the university including: What is freedom and what are its forms in the view of the commercialization of the market of educational services and research?
Keywords: szkolnictwo wyższe; wolność; nauka; uniwersytet